Time to first antibiotic and mortality in adults hospitalised with community-acquired pneumonia: a matched-propensity analysis. Issue 6 (11th November 2015) - Daniel, Priya; Rodrigo, Chamira; Mckeever, Tricia M; Woodhead, Mark; Welham, Sally; Lim, Wei Shen
Abstract : A matched-propensity analysis of national data from the British Thoracic Society community-acquired pneumonia audit was conducted (n=13 725). Overall, time to first antibiotic (TFA) was ≤4 h in 63%. Adjusted 30-day inpatient (IP) mortality was lower for adults with TFA ≤4 h compared with TFA >4 h (adjusted OR 0.84, 95% CI 0.74 to 0.94; p=0.003). Increasing TFA was associated with greater OR of 30-day IP mortality (p value for trend=0.001), but no TFA threshold was evident. Although we found an association between TFA and mortality, we cannot say whether this is causal or whether TFA might just be a quality measure for overall or other processes of care.